Rear view of the Sitaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here is the rear view of the Sitaleshwar Temple in the Chandrabhaga temple complex. The jangha (wall) of the temple has bhadra (central projections or offsets) on all three sides that are comparatively larger than other temples of that period. While these once housed sculptures of deities, they are presently empty.